PENERAPAN PEMBELAJARAN STUDYSASTER PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MASA PANDEMI COVID-19 DI SEKOLAH DASAR NEGERI SUKAJAYA 04 CIBITUNG - irfan syahrudi; Iwan Hermawan; Kasja Eka Waluyo (Universitas Islam Madura, 2023)
The rise of the Covid-19 virus which can cause death with very fast transmission in the community including in the school environment such as teachers, students and teaching staff, such as not yet obeying the regulations for preventing Covid-19 and using masks and washing hands and keeping a distance in every activity in the school environment is a focus of separate research. Therefore, this study aims to describe the process of implementing studysaster learning internalization in Islamic religious education subjects in the era of the co-19 pandemic at SDN Sukajaya. The research method used in this study is descriptive qualitative which describes all actions as well as events and phenomena carried out by the subjects studied in the implementation of this study, the data collection method used is interview, observation and analysis of documentation data which is then reduced and analyzed by the researcher before drawing a valid conclusion. While the research results obtained in the field are 1) Making posters for the prevention of Covid-19 which are inserted in Islamic religious subjects at school, with these results students can educate students in order to break the chain of distribution and transmission of Covid-19 to the surrounding community and society at large. 2) Prevention of Covid-19 is also carried out by way of education inserted in the middle of the lesson activities. Thus the implication of this research is that PAI learning can be developed with various methods including nurse studies for the sake of successful learning.